Additive Main effect and Multiplicative Interaction (AMMI) model analysis for yield performance and G×E interaction in a multi-environmental trial of aromatic fine rice in Bangladesh - Islam, Shams Shaila; Hasan, Ahmed Khairul; Khaldun, Abul Bashar Mohammad; Nazir, Novizar (Journal of Cereal Research, 2021)
The problem of genotype-environment interaction (G×E) ininterpreting multilocus trial analyses and predicting genotypeperformance can be mitigated by applying Additive Main effect andMultiplicative Interaction (AMMI) model analysis. The model AMMIwas used in the present study to determine the effect of genotype,environment, and their interaction, to determine the extent of G×Einteraction and to identify the factors contributing to G×E interactionfor the best yielding aromatic fine rice genotype grown in fourdifferent districts in Bangladesh. Analysis of variance showed thatthe effect of genotypes, environments, G×E interactions were highlysignificant for plant height, days to maturity, panicles length, grainyield. Result showed grain yield had highly significant differences forenvironmental traits like (soil properties, phenological, genotypes)with their interactions which indicated that environments weredifferent and changeability with the genotypes. Large variations intotal P, Fe and rainfall identified as the main cause of the observedinteraction. Here, Genotype BRRI Dhan34 had the highest mean grainyield values over four locations, respectively. In AMMI model, amongfour locations Dinajpur with Nilphamari were the majority responsiveenvironments and Dinajpur was the most adjacent responsive location.Therefore, location Dinajpur with BRRI Dhan34 genotype could beconsidered as a better combination for higher grain yield among theten aromatic fine rice genotypes.